2020
DOI: 10.1039/d0ra08894c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of multi-type carbon doped and modified nano-TiO2 for enhanced visible-light photocatalysis

Abstract: The synergistic modification of nano-TiO2 by multi-type carbon species results in excellent and stable visible-light photocatalytic degradation activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…38 In addition, the Ti 2p 1/2 peak of CC-OV-TiO 2 is 0.1 eV higher than that of OV-TiO 2 , which is also directly related to the electron-withdrawing effect of −COO − groups. 24 Overall, the intensity of the Ti 2p peaks of OV-TiO 2 is significantly higher than that of CC-OV-TiO 2 , which should be attributed to the fact that more Ti atoms are exposed after the surface carbon species of OV-TiO 2 are removed by photothermal catalysis.…”
Section: Industrial and Engineeringmentioning
confidence: 88%
See 1 more Smart Citation
“…38 In addition, the Ti 2p 1/2 peak of CC-OV-TiO 2 is 0.1 eV higher than that of OV-TiO 2 , which is also directly related to the electron-withdrawing effect of −COO − groups. 24 Overall, the intensity of the Ti 2p peaks of OV-TiO 2 is significantly higher than that of CC-OV-TiO 2 , which should be attributed to the fact that more Ti atoms are exposed after the surface carbon species of OV-TiO 2 are removed by photothermal catalysis.…”
Section: Industrial and Engineeringmentioning
confidence: 88%
“…However, there are few studies on the doping and modification of TiO 2 by functionalized carbon species. In our previous work, it has been found that the modification of TiO 2 using carboxylated carbon species can induce a substantial downward shift of the VB edge while promoting band gap narrowing. , Therefore, the modification of oxygen-deficient TiO 2 by using carboxylated carbon species may be beneficial to alleviate the rise of the VB edge caused by the defect energy level and then make it possible to construct a TiO 2 photocatalytic system with a narrow bandgap and low VB.…”
Section: Introductionmentioning
confidence: 99%
“…Visible-Light Photocatalytic Performance. As we reported previously, 14,15 Under the irradiation of 20 W selfmade LED lamp (wavelength ranged from 420 to 500 nm, and a glass filter (λ ≥ 420 nm) was used to filter shortwavelength ultraviolet light (Figure S1)), the performance of photocatalyst was evaluated by using MO aqueous solution containing 30 mL 20 ppm. In a standard degradation experiment, 0.1 g of the prepared catalyst was introduced into the aqueous solution of MO, and the solution was stirred in the dark for 60 min to establish adsorption−desorption equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…3,18 The % photoreduction percentage (PRP) was calculated using the following formula:where A 0 represents the initial absorbance at time 0 after the treatment in dark, just before light is switched on and A t is the absorbance after photoreduction process at time t . For determination of the possible reactive species during the photocatalytic reduction, experiments were repeated with TBA, AgNO 3 , and p -BQ instead of CA to capture hydroxyl radical (˙OH), 19–21 electrons (e − ), 22 and superoxide radical (O 2˙ − ), 18,19,22–26 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Specically, a cOH radical quencher (tert butyl alcohol (TBA)) and a O 2 c − radical quencher (p-benzoquinone (BQ)) were added. [18][19][20][21][22][23][24][25][26] The photoreduction rate of Cr(VI) decreases when each of these radical quenchers is added (Fig. 5b), indicating that both cOH radicals and O 2 c − radicals are produced by CBTO and are involved in the photoreduction of Cr(VI).…”
Section: Cbto As a Functional Materials In Photocatalytic Application...mentioning
confidence: 99%